Experience of the nursing professional in his relationship with the student during clinical practice - Elizalde-Ordoñez, Humberto (Universidad de Sonora, 2021)
Introduction: The interaction between the nursing students and the clinical nurses in the practice place influences their learning process, generating possibilities, mental models that will very likely be replicated once the students graduate. Objective: Understand the experience of the nursing professional and their relationship with the student during their medical practice. Methodology: Qualitative phenomenological study using snowball sampling, until reaching data saturation. Data collection throughout non-structured in-depth interviews; the interviews were recorded and literally transcribed for analysis. Results: 19 Nurses participated (4 men and 15 women) which were identified into two categories: currently-around and coexisting with the students. Conclusions: The Nursing professional considered that the students should understand and work in a collaborative manner in order to take advantage of their experience and knowledge, prevent crushing remarks, as well as respect individuality. A Good relationship between the students and clinical nurses could lead to a more beneficial practice.